Following the unusual breathing behaviour of 17O-enriched mixed-metal (Al,Ga)-MIL-53 using NMR crystallography - Rice, Cameron M; Davis, Zachary H; McKay, David; Bignami, Giulia P M; Chitac, Ruxandra G; Dawson, Daniel M; Morris, Russell E; Ashbrook, Sharon E (Physical chemistry chemical physics, 2020)
The breathing behaviour of 17O-enriched (Al,Ga)-MIL-53, a terephthalate-based metal-organic framework, has been investigated using a combination of solid-state nuclear magnetic resonance (NMR) spectroscopy, powder X-ray diffraction (PXRD) and first-principles calculations. These reveal that the behaviour observed for as-made, calcined, hydrated and subsequently dehydrated mixed-metal MIL-53 materials differs with composition, but cannot be described as the compositionally weighted average of the breathing behaviour seen for the two end members. Although the form of MIL-53 adopted by the as-made material is independent of metal composition, upon calcination, materials with higher levels of Al adopt an open pore (OP) form, as found for the Al end member, but substitution of Ga results in mixed pore materials, with OP and narrow pore (NP) forms co-existing. Although the Ga end member is prone to decomposition under the calcination conditions used, a low level of Al in the starting synthesis (5%) leads to an OP mixed-metal MOF that is stable to calcination. Upon hydration, all materials almost exclusively adopt a closed pore (CP) structure, with strong hydrogen bonding interactions with water leading to two distinct resonances from the carboxylate oxygens in 17O NMR spectra. When dehydrated, different framework structures are found for the two end members, OP for Al-MIL-53 and NP for Ga-MIL-53, with the proportion of NP MOF seen to increase systematically with the Ga content in mixed-metal materials, in contrast to the forms seen upon initial calcination. 17O NMR spectra of mixed-metal MIL-53 materials show an increased preference for clustering of like cations as the Ga content increases. This is not a result of the small-scale dry gel conversion reactions used for enrichment, as a similar cation distribution and clustering is also observed for (Al0.5,Ga0.5)-MIL-53 synthesised hydrothermally and enriched with 17O via post-synthetic steaming.